Analysis of the Commutative Method Approach on English Thesaurus for Developing Synonym Sets - Arini Rohmawati; Moch. Arif Bijaksana; Kemas Muslim Lhaksmana (School of Computing, Telkom University, 2019)
WordNet is a lexical database for languages, the difference between WordNet and dictionaries in general is that WordNet focuses on the synonyms. The main unit of WordNet is synonym set (synset), synset is a set of one or more words that have the same meaning and certainly can be replaced in certain contexts. Synset is a very important element in implementing WordNet. In this paper, an analysis of the synonym extraction process is carried out by using commutative approach, the data test obtained from the Oxford Paperback Thesaurus by taking 51 word entries. Commutative method has similar characters with synonym set, synonym set can replace each other in certain contexts. The data test extraction process is carried out until the performance measurement evaluation process using F1Score. The system generates synonym sets that matched with the manual extraction, the result of F1Score between the program and Princeton synonym sets are worth 10%.